2000
DOI: 10.1902/jop.2000.71.6.974
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Dose‐ and Time‐Dependent Effect of Basic Fibroblast Growth Factor on the Gene Expression of Collagen Type I and Matrix Metalloproteinase‐1 by Periodontal Ligament Cells in Culture

Abstract: These results suggest that bFGF is one of the important regulators involved in the active remodeling of col I in the periodontal ligament and possibly in other connective tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
33
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 29 publications
8
33
0
1
Order By: Relevance
“…75,76 Flexor tendon tenocytes subjected to shear stress also demonstrated downregulation of type I collagen expression, 77 as did bone marrow stem cells seeded on a composite of tendon slices. 56 The presence of LDM significantly increased cell proliferation and matrix synthesis.…”
Section: Little Et Almentioning
confidence: 99%
“…75,76 Flexor tendon tenocytes subjected to shear stress also demonstrated downregulation of type I collagen expression, 77 as did bone marrow stem cells seeded on a composite of tendon slices. 56 The presence of LDM significantly increased cell proliferation and matrix synthesis.…”
Section: Little Et Almentioning
confidence: 99%
“…18 Fibroblast growth factors (FGFs) are a large family of polypeptide growth factors that regulate the secretion of various extracellular matrix (ECM) proteins, which contribute to the formation of new blood vessels. 19,20 Fibroblast growth factor 2 (FGF2) is a potent mitogen in a variety of cells and is effective in regulating the proliferation and ECM-related gene expression of fibroblasts, 21,22 the most common cell type in peri-implant gingival connective tissue.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests MMP-1 is associated with pro-angiogenic events (Blackburn and Brinckerhoff, 2008). Research regarding the effects of bFGF on MMP-1 expression has demonstrated that bFGF administration increase MMP-1 expression in human periodontal ligament cells (Palmon et al, 2000). An increase of MMP-1 protein was also observed when bFGF was added to human skin fibroblasts (Xie et al, 2008).…”
Section: Discussionmentioning
confidence: 99%